ผลของการจัดการกับอาการร่วมกับการนวดแผนไทยต่อความเหนื่อยล้าในผู้ป่วยไตวายเรื้อรังระยะสุดท้ายที่รับการฟอกเลือดด้วยเครื่องไตเทียม - วาทินี ศรีไทย (จุฬาลงกรณ์มหาวิทยาลัย, 2005)
The purpose of this experimental research was to study the effect of symptom management combined with Thai traditional massage. The sample was 40 patients receiving hemodialysis twice per week, at the Hemodialysis Unit, Kidney Foundation of Thailand, Galyani Valthana building, Priests Hospital, which were matched into 20 pairs considering age and education as the selected variables. Then the subjects were randomly assigned into one experimental group and one control group. The experimental group received nursing care according to symptom management concept combined with Thai Traditional massage, while the control group received rountine nursing care. Research instruments were a health teaching plan with a patient manual which were tested for content validity by experts. Fatigue Questionnaire according to Piper et al. (1998) was used in data gathering process. The reliability of this questionnaire (Cronbach s alpha coefficient) was .93. Descriptive statistics and t-test were used in data analysis. Major research findings were as follows : 1. The fatigue of end stage renal failure patients receiving hemodialysis in experimental group after receiving nursing care according to symptom management concept combined with thai traditional massage was significantly lower than before experiment, at the .05 level. 2. After the experiment the fatigue of end stage renal failure patients receiving hemodialysis in the experimental group was significantly lower than that of the patients in the control group